Nitric Oxide Synthase Regulates Gut Microbiota Homeostasis by ERK-NF-κB Pathway in Shrimp - Hong, Pan-Pan; Zhu, Xiao-Xu; Yuan, Wen-Jie; Niu, Guo-Juan; Wang, Jin-Xing (Frontiers in Immunology, 2021)
The gut microbiota is a complex group of microorganisms that is not only closely related to intestinal immunity but also affects the whole immune system of the body. Antimicrobial peptides and reactive oxygen species participate in the regulation of gut microbiota homeostasis in invertebrates. However, it is unclear whether nitric oxide, as a key mediator of immunity that plays important roles in antipathogen activity and immune regulation, participates in the regulation of gut microbiota homeostasis. In this study, we identified a nitric oxide synthase responsible for NO production in the shrimp Marsupenaeus japonicus. The expression of Nos and the NO concentration in the gastrointestinal tract were increased significantly in shrimp orally infected with Vibrio anguillarum. After RNA interference of Nos or treatment with an inhibitor of NOS, L-NMMA, NO production decreased and the gut bacterial load increased significantly in shrimp. Treatment with the NO donor, sodium nitroprusside, increased the NO level and reduced the bacterial load significantly in the shrimp gastrointestinal tract. Mechanistically, V. anguillarum infection increased NO level via upregulation of NOS and induced phosphorylation of ERK. The activated ERK phosphorylated the NF-κB-like transcription factor, dorsal, and caused nuclear translocation of dorsal to increase expression of antimicrobial peptides (AMPs) responsible for bacterial clearance. In summary, as a signaling molecule, NOS-produced NO regulates intestinal microbiota homeostasis by promoting AMP expression against infected pathogens via the ERK-dorsal pathway in shrimp.